Psychodynamics: A Representation of the Ego Counseling Framework in Mental Health Treatment - Al Habsy, Bakhrudin; Zaein, Maulana Riqfi; Hikam, Ahmad Fathkul; Fauzan, Hafidz Wahyu (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
The purpose of this study is to represent the Ego Counseling Framework (Psychodynamics) in mental health treatment. This research used a qualitative method of literature study. The literature selection process was conducted in two stages. First, screening based on title and abstract. The literature that passed the initial selection was then read in its entirety to assess its eligibility and relevance to the research topic. Data Analysis Qualitative data from the selected literature was analyzed using a qualitative metasynthesis approach. The results of the study obtained the conclusion that the role of ego counseling in mental health treatment emphasizes on understanding the ego in including (1) Understanding yourself; (2) personality improvement; (3) improvement of social relationships; (4) improvement of applicable personality; (5) improvement of career choice skills; (6) improvement of self-awareness skills. The implications of the results of this study as a source of reading knowledge in the field of guidance and counseling, namely regarding the ego counseling framework (psychodynamics) in handling mental health.